ROOT CAUSE ANALYSIS ON HOSPITAL STANDARDS AND JOINT COMMISSION INTERNATIONAL STANDARDS: A COMPARATIVE STUDY - Bella Putri Lanida; Tito Yustiawan; Sylvy Medtasya Dzykryanka (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: Healthcare Associated Infections (HAIs) are infections that patients caught during medical treatment and health care. Prevention and control of infection will lead to patient safety, which ultimately has an impact on efficiency, management of health care facilities, and improvement of service quality. Infection can be controlled by identifying the causes. One method to achieve this goal is the Root Cause Analysis (RCA).Aim: This study aims to analyze the implementation of Root Couse Analysis (RCA) conducted by the Infection Prevention and Control Committee at the Mother and Child Hospital of Kendangsari MERR Surabaya.Method: This is a quantitative observational research that utilizes descriptive data analysis. This study is a cross sectional study and its results are presented narratively.Results: Results show that the Joint Commission International Standard 2015 version of RCA was not fully implemented at the Mother and Child Hospital of Kendangsari MERR Surabaya. Some methods, such as the fishbone and Plan-Do-Study-Action (PDSA), were not implemented. Limited resources became the contributing factor.Conclusion:  Infection Prevention and Control Committee at the Mother and Child Hospital of Kendangsari Merr Surabaya has implemented 9 out of 21 RCA steps of the Joint Commission International Standard 2015. The hospital needs to use other methods as an addition to the 5 Why’s in implementing RCA, such as fishbone diagrams and Plan-Do-Study-Action (PDSA), for problem solving planning. Keywords: Root Cause Analysis (RCA), HAIs, Infection prevention and control.